2017
DOI: 10.1101/184523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective effect of estrogen against intervertebral disc degeneration is attenuated by miR-221 through targeting estrogen receptor

Abstract: Intervertebral disc degeneration (IDD) is a multifactorial disease that associates apoptosis, senescence and calcification of cartilage cells, inflammatory response and alterations in the extracellular matrix. Previous documents imply that estrogen and miR-221 may be involved in IDD. This study further investigated their regulatory mechanisms underlying IDD. Normal and degenerated cartilaginous endplates (CEP) tissues were isolated surgically from juvenile patients with idiopathic scoliosis and adult patients … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Study by Maneix et al, [8] shows that 17beta-estradiol (E2) up-regulates cartilage marks including type II collagen gene (COL2A1) and Sox-9 in dedifferentiated articular chondrocytes in osteoarthritis, suggesting the promoting effect of 17β-E2 on chondrocyte redifferentiation. But, a tissue engineering study found that 17β-E2 inhibits chondrogenic differentiation of mesenchymal stem cells via activating G protein-coupled receptor 30 [9]. Estrogen presumably confers different effect on cartilage differentiation, depending on cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Study by Maneix et al, [8] shows that 17beta-estradiol (E2) up-regulates cartilage marks including type II collagen gene (COL2A1) and Sox-9 in dedifferentiated articular chondrocytes in osteoarthritis, suggesting the promoting effect of 17β-E2 on chondrocyte redifferentiation. But, a tissue engineering study found that 17β-E2 inhibits chondrogenic differentiation of mesenchymal stem cells via activating G protein-coupled receptor 30 [9]. Estrogen presumably confers different effect on cartilage differentiation, depending on cell types.…”
Section: Introductionmentioning
confidence: 99%